1998
DOI: 10.1111/j.1095-8649.1998.tb01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of flood control schemes on river fish migrations and species assemblages in Bangladesh

Abstract: A mark-recapture programme at the Pabna Irrigation and Rural Development Project (PIRDP) site in NW Bangladesh showed that Catla catla, Channa striata and Wallago attu migrated through the sluice gates, both with and against prevailing currents in different season, while the smaller Anabas testudineus, Glossogobius giuris and Puntius sophore did not. Species assemblages were significantly different inside and outside the flood control, drainage and irrigation (FCDI) schemes, with up to 25 species absent or les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 6 publications
5
29
0
Order By: Relevance
“…This downstream migration pattern had already been documented in a study by Halls et al (1998) of C. striata in Bangladesh. Alternatively, the low variability observed in these three populations could also be the result of a historical bottleneck event that may have almost eradicated these populations.…”
Section: Discussionsupporting
confidence: 68%
“…This downstream migration pattern had already been documented in a study by Halls et al (1998) of C. striata in Bangladesh. Alternatively, the low variability observed in these three populations could also be the result of a historical bottleneck event that may have almost eradicated these populations.…”
Section: Discussionsupporting
confidence: 68%
“…At the end of the monsoon, these fishes move in the opposite direction, from floodplains through the tributaries, and eventually to the Mekong mainstream, where many fishes spend the dry season in deep pools (Poulsen & Jørgensen 2001). Halls, Hoggarth & Debnath (1998) indicated that the floodplain habitat is necessary to the silurids to complete their life cycle. Thus, opening the sluice gates periodically is the recommended strategy to increase the accessibility of migrant fishes to the upstream, floodplain area (Hoggarth, Cowan, Halls, Aeron-Thomas, Garaway, Payne & Welcomme 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, as well as directly restricting fish passage, tide gates can indirectly affect fish behaviour and community composition through alterations to the instream environment, particularly upstream of the gates. By blocking the normal bi-directional movement of water the upstream hydrological regime is altered; the velocity, turbulence and pattern of freshwater drainage is modified; the normal gradual transition in salinity is disrupted; and the stagnation of freshwater above the tide gates can result in sedimentation and increased water temperatures (Pollard and Hannan, 1994;Kroon and Ansell, 2006;Halls et al, 1998). This is likely to interrupt rheotactic and olfactory cues for migrating fish species (e.g.…”
Section: Introductionmentioning
confidence: 97%